Consumers' Perspectives on the Design of a New Digital Frailty Education Course, ‘Focus on Frailty’: A Qualitative Co‐Design Study - Kristiana Ludlow; Benignus Logan; Jhalak Arora; Sarah Martin; Elizabeth Miller; Ruth E. Hubbard; Nicola Warren; Olivia Gallagher; Rosemary Saunders (Health Expectations, 2025)
ABSTRACT Introduction Frailty‐focused care in hospitals is hindered by systemic barriers, ageism and stereotypes about older adults and frailty. There is a need for frailty education to increase healthcare professionals' and students' understanding of frailty. Objective As part of a larger study to co‐design a new digital frailty education course, ‘Focus on Frailty’, this study aimed to explore consumers' and caregivers' perspectives on (i) how frailty and older adults should be represented in frailty education and (ii) what healthcare professionals should be taught about caring for older adults and people who are frail in hospitals. Design This was a qualitative co‐design study. Setting and Participants Participants (n = 25) were older Australians, people living with frailty and family caregivers (collectively, ‘consumers’) who had interacted with the hospital system. This study was conducted in Australia via Zoom and telephone. Methods Participants engaged in focus groups or individual interviews and completed a demographic questionnaire and a Research Engagement Feedback Survey. Qualitative data were inductively analysed using template analysis (codebook thematic analysis). Quantitative demographic data were analysed using descriptive statistics. Results Seven themes were identified: (1) Consumers' understanding of frailty as loss, deterioration and vulnerability; (2) Utilise a holistic approach to frailty care; (3) Dispel stereotypes; (4) Value consumers' lived experience expertise; (5) Include diverse representation and educate for diversity; (6) Promote meaningful interactions; and (7) Practice care coordination. Discussion Participants acknowledged the multifaceted nature of frailty, advocating for holistic frailty education that considers physical, social, emotional, cognitive, financial and spiritual aspects. They described the importance of representing real‐world scenarios and stories, images and videos of real people that reflected the diversity of lived experience. Participants wanted ‘Focus on Frailty’ to include education on individualised care; looking beyond the acute situation; multidisciplinary care coordination that involved informal caregivers; overcoming stereotypes and ageism; and meaningfully interacting with older adults and people who are frail. Conclusions Consumers wanted to be represented in frailty education in a way that elevates lived experience and celebrates diversity. They expressed that healthcare professionals should be taught to avoid stereotypes, coordinate multidisciplinary care and engage in meaningful interactions with patients. Consumer‐focused recommendations for designing frailty education were generated. Patient or Public Contribution E.M., a consumer partner, contributed to the study design, focus group/interview guide, ethics application and participant information and consent forms. E.M. attended some of the focus groups and contributed to the interpretation of study findings. She also contributed to manuscript revisions. Twenty‐five consumers (family caregivers, older adults and people with lived experience of frailty) participated in focus groups and interviews. Participants shared their perspectives on frailty and contributed to the co‐design of a new digital frailty education course for healthcare professionals and students.